A Strength Design Method of Cemented Backfill with a High Aspect Ratio - Zhi-zhihui Wang; Ai-xiang Wu; Hong-jiang Wang (Advances in Civil Engineering)
To calculate the required strength of a cemented backfill with high aspect ratio, the confirmation of lateral pressure is fundamental and needs to be determined first. As for the backfill with a high aspect ratio of height to length, the shape of the slip surface is not straight when in the active state due to the limited space, which is different from the general backfill. For this reason, a formulation of the slip surface with a curved shape and a lateral pressure calculation method based on this curved slip surface were proposed. The proposed equation of the slip surface is affected by the geometry parameters of the backfill, internal friction angle of the backfill, and the friction angle of the backfill-rock interface. Then, by the combination of the minor principal stress trajectory method and the horizontal slice method, an ordinary differential equation of stresses was established and then solved numerically. Finally, the method based on Mitchell’s three-dimensional limit equilibrium model was used to calculate the required strength of the cemented backfill. The calculated results were compared with previous studies and validated with numerical models. The results showed good consistency for the backfills with high aspect ratios.